Magnetic Resonance Elastography as Surrogate Marker of Interstitial Fibrosis in Kidney Transplantation: A Prospective Study. Issue 11 (24th November 2022) - Chauveau, Bertrand; Merville, Pierre; Soulabaille, Bruno; Taton, Benjamin; Kaminski, Hannah; Visentin, Jonathan; Vermorel, Agathe; Bouzgarrou, Mounir; Couzi, Lionel; Grenier, Nicolas
Key Points: Magnetic resonance elastography–derived stiffness does not directly reflect the extent of fibrosis in kidney transplantation. Mean magnetic resonance elastography–derived stiffness displays high interpatient variability, even in allografts without significant fibrosis, suggesting a strong influence of confounding factors. Visual Abstract: Abstract : Background: Fibrosis progression is a major prognosis factor in kidney transplantation. Its assessment requires an allograft biopsy, which remains an invasive procedure at risk of complications. Methods: We assessed renal stiffness by magnetic resonance elastography (MRE) as a surrogate marker of fibrosis in a prospective cohort of kidney transplant recipients compared with the histologic gold standard. Interstitial fibrosis was evaluated by three methods: the semi-quantitative Banff ci score, a visual quantitative evaluation by a pathologist, and a computer-assisted quantitative evaluation. MRE-derived stiffness was assessed at the superior, median, and inferior poles of the allograft. Results: We initially enrolled 73 patients, but only 55 had measurements of their allograft stiffness by MRE before an allograft biopsy. There was no significant correlation between MRE-derived stiffness at the biopsy site and the ci score ( ρ =–0.25, P =0.06) or with the two quantitative assessments (pathologist: ρ =–0.25, P =0.07; computer assisted: ρ =–0.21, P =0.12). We observed negative correlations between the stiffness of both the biopsy site and the whole allograft, with either the glomerulosclerosis percentage ( ρ =–0.32, P =0.02 and ρ =–0.31, P =0.02, respectively) and the overall nephron fibrosis percentage, defined as the mean of the percentages of glomerulosclerosis and interstitial fibrosis ( ρ =–0.30, P =0.02 and ρ =–0.28, P =0.04, respectively). At patient level, mean MRE-derived stiffness was similar across the three poles of the allograft (±0.25 kPa). However, a high variability of mean stiffness was found between patients, suggesting a strong influence of confounding factors. Finally, no significant correlation was found between mean MRE-derived stiffness and the slope of eGFR ( P =0.08). Conclusions: MRE-derived stiffness does not directly reflect the extent of fibrosis in kidney transplantation.